PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN HULU SUNGAI UTARA - Yudi Rahman; f a k h r i; Fauziannor Fauziannor; Novi Indriyanti (KINDAI, 2026)
ABSTRACT: This study aims to analyze the influence of human resource capacity, information technology utilization, and the government's internal control system on the quality of the Hulu Sungai Utara Regency Government's financial reports, either simultaneously, partially, or predominantly. The study employed a quantitative approach with descriptive and explanatory research methods. The study population consisted of 78 financial employees in 39 regional government agencies (SKPD). Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that simultaneously, human resource capacity, information technology utilization, and the internal control system significantly influence the quality of financial reports. Partially, all three variables also exerted a positive and significant influence, with coefficients of 0.181 (HR), 0.227 (IT), and 0.575 (SPIP), respectively. The most dominant variable was the internal control system, with a beta value of 0.791. The coefficient of determination indicates that 58% of the variation in financial report quality can be explained by these three variables, with the remainder influenced by other factors. These findings indicate that the quality of local government financial reports is largely determined by the synergy between human resource competency, information technology optimization, and the effectiveness of internal control systems. Therefore, improving the quality of financial reports requires a focus on strengthening human resource capacity, developing integrated technology systems, and strengthening the ongoing implementation of internal controls. Keywords: Human Resources Capacity, Information Technology, SPIP, Financial Report Quality, Regional Government